2005
DOI: 10.1128/jvi.79.3.1842-1852.2005
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Snakehead Rhabdovirus Infection in Zebrafish ( Danio rerio )

Abstract: The zebrafish, Danio rerio, has become recognized as a valuable model for the study of development, genetics, and toxicology. Recently, the zebrafish has been recognized as a useful model for infectious disease and immunity. In this study, the pathogenesis and antiviral immune response of zebrafish to experimental snakehead rhabdovirus (SHRV) infection was characterized. Zebrafish 24 h postfertilization to 30 days postfertilization were susceptible to infection by immersion in 10 6 50% tissue culture infective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
98
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(105 citation statements)
references
References 50 publications
4
98
1
1
Order By: Relevance
“…Our results probably explain why, in a model of snakehead rhabdovirus infection, Phelan et al (14) only found a very modest zIFN mRNA increase despite strong MX induction.…”
Section: Zifn Induction Involves Alternative Splicing and Promoter Usagesupporting
confidence: 58%
See 1 more Smart Citation
“…Our results probably explain why, in a model of snakehead rhabdovirus infection, Phelan et al (14) only found a very modest zIFN mRNA increase despite strong MX induction.…”
Section: Zifn Induction Involves Alternative Splicing and Promoter Usagesupporting
confidence: 58%
“…Although human and mice have a single gene coding for IFN-␥, some teleosts (including zebrafish) have more than one gene, but in all instances these genes have three introns. In contrast, the designation of fish virus-induced IFNs has been more problematic and most authors merely called them "IFN" (13,14). Based on their similarity with mammalian IFNs some authors call them type I IFNs (15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…Although induction of type I IFNs is apparent after virus infection or treatment with killed viruses, the kinetics of induction vary dependent on the virus, host and infection route (McBeath et al 2007;Robertsen 2008). For example, zebrafish infected with snakehead rhabdovirus for 7 days exhibited maximal accumulation of IFN messenger RNA (mRNA; Phelan et al 2005). Unmethylated CpG containing DNA also activates IFN gene transcription in Atlantic salmon leucocytes (Pedersen et al 2006;Strandskog et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…63 -66 It is also easier to standardize husbandry factors for smaller animals, so reproducibility between studies on laboratory fish is therefore easier to attain. However, the extrapolation of the results from, for example, zebrafish to salmonids is often difficult 67 as these species are more distantly related than the mouse is to man. Performing experiments directly on the production animals is also essential in many cases, such as in vaccine development.…”
Section: Laboratory Fish Modelsmentioning
confidence: 99%